Revitalization of Integrated Thematic Material to Improve the Learning Process - Afriani, Karmela (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2017)
The aim of this research is to improve students' abilities in the learning process, especially in integrated thematic learning material in class IV. This research method is Research and Development (R&D). This development research procedure uses the ADDIE model. This research instrument is a validation questionnaire for material experts, media experts, language experts and practitioner experts and interview sheets for students and class teachers. The results of this research are: (1) Revitalization of integrated thematic material to improve the learning process for class IV with theme 2 "Always Save Energy". (2) The level of validity of the integrated thematic material revitalization module for class IV Elementary School obtained from the material expert validator with a score of 3.6 is in the very valid category with a percentage of 72%, the media expert validator with a score of 4.3 is in the very valid category with a percentage of 86 %, language expert validators with a value of 4.82 are in the very valid category with a percentage of 96.3%. (3) The level of practicality of the module developed with expert practitioners carried out by 1 class IV B elementary school teacher was obtained with a score of 4.8, including the very practical category. The conclusion of this research resulted in a product in the form of teaching materials for a revitalization module of integrated thematic material for class IV elementary schools. which is suitable for use in the learning process.